English as a Foreign Language students’ diagnosis of dyslexia in a context of community service - Castro Pucuji , Estefany Maribel; Granja Rubio , Jessica Dayanna; Abata Checa , Fanny Mercedes (Arandu UTIC, 2025)
Dyslexia is a learning disability that affects people of all ages, including children, teenagers, and adults, and it impacts their reading and writing abilities. It can influence both syllabic and phonetic awareness. Common traits include difficulties with fluency, reading, and spelling. The goal was to identify students with dyslexia in a community service setting. A qualitative methodology with a descriptive approach was used. The instrument employed was the PECFO test, which has two parts: syllable awareness and phonetic awareness. This tool was used to diagnose students attending a center, aged between 4 and 7 years. The results showed that 7 students exhibited characteristics of dyslexia. They scored within the 10th percentile according to the table, indicating they have dyslexia. These students represented 21.88% of the sample, with 15.63% being female and 6.25% male. The conclusion is that these students have deficiencies in syllabic and phonetic awareness, which hinder their reading and writing skills, leading to slower learning.